Improving the Quality of Learning Through the Application of Group Investigation Model for Economic Education Study Program Students - Zainal Arifin; Tjetjep Yusuf Afandi; Elis Irmayanti (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The quality of learning is something that needs to be improved continuously. The implementation and achievement of an optimal learning process is use to gain the achievement of the expected learning objectives so learning activities can run effectively. With the application of the group investigation learning model, it is expected to be able to improve the quality of learning in the classroom since the group investigation method. By using this model, students are able to express themselves, improve critical thinking and other abilities that can support group learning or discussion. The main objective of this research was to improve the quality of learning through the application of the group investigation model to students. The research method used was classroom action research with two cycles of action. Furthermore, comparative data analysis was also used to compare learning in each cycle. The result of this research was an improvement in the learning process carried out by students from cycle I to cycle II, especially in the aspects of the research objectives. There was an increase in the first cycle, the average value was 68.22% and the average value in the second cycle was 83.33% with the correlation level from the first cycle and the second cycle was 0.619 or 61.9%. And the level of significance known from the data Sig.(2-tailed) was 0.000 <0.05 showed there was a difference from cycle I to cycle II in improving the quality of learning by applying the group investigation model.